Antarctic geomagnetic field changes in the last century - Melnyk, G.; Bakhmutov, V.; Shenderovska, O. (Ukrainian Antarctic Journal, 2014)
The features of the geomagnetic field changes in the Antarctic in the XX century have been defined, according to calculations by the IGRF (International Geomagnetic Reference Field) and observations at the observatories. It is found that in the southern hemisphere, the full vector of the geomagnetic field F decreases faster than in the north. The amplitude and rate of change increases toward lower latitudes in the northern hemisphere and to the highest in the south. In the southern hemisphere in the structure of the secular variation are three period changes similar to those in the north. West and East Antarctica have different dynamics of change of the geomagnetic field. Its intensity increases in the east and decreases to the west. The most intensive decrease of the geomagnetic field intensity is fixed according to the observatory AIA, which is in the negative focus of secular variation in Western Antarctica.